MEDICAL AFFAIRS EFFICIENCY IN PHARMA – A PRAGMATIC APPROACH TO SUCCESS - José Aleixo Dias (Revista Portuguesa de Farmacoterapia, 2014)
Along recent years Pharma operations became increasingly complex. Trying to adapt to the requests of a fast changing and demanding environment, companies moved from the standard medical, marketing and sales structure to a much more complex puzzle of units, departments, internal and external reporting lines. Along with these, the number of functions increased so much that titles became confused for customers as for colleagues. The number of systems and tools grew alike; some are useful while others not compatible or redundant. The medical structure which was minimal two decades ago, increased to meet the requirements for scientific evidence, both from prescribers and payers. The roles of these medical affairs (MA) functions, the way these are organized, the processes of interaction with other relevant players, their contribution to capture insights and translate these into actions, their reporting lines and the impact generated for the business and to the customers, are very much under discussion. Companies have been adopting different models to respond to these needs, but the change is constant, showing that most probably, the best fit has not yet been reached. The customer facing medical is a natural strategic evolution of the traditional MA role, demonstrating value, business alignment, integration and governance, which are essential pillars in building customer partnerships. This article describes the situation, and discusses pragmatic approaches to some of the most common challenges and issues, aiming to contribute to the improvement and effectiveness of the MA operations.